1998
DOI: 10.1111/j.1528-1157.1998.tb01281.x
|View full text |Cite
|
Sign up to set email alerts
|

NER Rat Strain: A New Type of Genetic Model in Epilepsy Research

Abstract: Summary:Purpose: We characterized and evaluated as an animal model of epilepsy NER, a new epileptic rat strain, which was developed by inbreeding rats with spontaneous tonic-clonic seizures in a stock of Crj:Wistar.Methods: Animals were monitored through the inbreeding course, and video-EEGs were recorded selectively. External seizure-provoking stimuli were applied to NER and to a control parental strain. FI, F2, and backcross progenies were produced between NER and a nonepileptic unrelated strain. Pathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…The basal activity before seizures (1) and the stages of seizures were observed as follows: beginning of aberrant activity on electroencephalogram without behavioral changes (2); asymmetric wave with myoclonus (3); high-voltage wave with tonic-clonic convulsion (4); low-voltage wave with postictal flaccidness (5). The component of γ-wave (7–9 Hz) (2, 6.9%; 3, 19.4%; 4, 15.4%; 5, 10.0%) became rhythmic during seizures as reported previously [26].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The basal activity before seizures (1) and the stages of seizures were observed as follows: beginning of aberrant activity on electroencephalogram without behavioral changes (2); asymmetric wave with myoclonus (3); high-voltage wave with tonic-clonic convulsion (4); low-voltage wave with postictal flaccidness (5). The component of γ-wave (7–9 Hz) (2, 6.9%; 3, 19.4%; 4, 15.4%; 5, 10.0%) became rhythmic during seizures as reported previously [26].…”
Section: Resultssupporting
confidence: 83%
“…It is well known that epileptic seizures are closely linked to external stimuli in human. External stimui have been usually used for the analysis on tonic-clonic activity in spontaneous epilepsy animals [26], [33]. The hippocampal electroencephalogram during CQ (30 mg/kg)-induced convulsion was similar to that during sound-induced convulsions in NER reported previously [26].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our seizure-sensitive strain of gerbils does not show RBME in the absence of seizure-inducing stimuli, and it is thus possible that, when they receive a seizure-inducing stimulus, some transient phenomenon that inhibits GABA A receptor or brings similar situation occurs and starts RBME by a still unknown mechanism. Clarification of the mechanism underlying both types of RBME mentioned above and the possible roles of the SI may provide information on some of the stimulus-induced repetitive movements that are occasionally observed in epileptic animal species, including human beings [14,17,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Although information on the mechanisms of Kir4.1 channels underlying the control of seizure induction is very limited, NER, a hereditary animal model of GTCS [31][32][33][34][35] , showed a region-specific reduction in the Kir4.1 channel expression in the amygdala [30] (Table 1). While no mutational changes in the Kir4.1-coding gene (Kcnj10) were observed in NER, Western blot analysis of the samples obtained under interictal conditions revealed that the expressional level of Kir4.1 (but not Kir5.1 or Kir2.1) was selectively diminished in the occipito-temporal cortex and thalamus among 10 brain regions examined (e.g., frontal, parieto-temporal and occipito-temporal cortex, hippocampus, striatum, thalamus, hypothalamus, midbrain, pons-medulla oblongata and cerebellum).…”
Section: Structure and Drug Interaction Of Kir41 Channelsmentioning
confidence: 99%